Cultural Adaptation, Social Integration, and Health Outcomes among Immigrant Communities in Kullu District, Himachal Pradesh (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This paper examines links between cultural adaptation, social integration, and health outcomes among immigrant and seasonal migrant populations in Kullu district, Himachal Pradesh, using secondary, district-level data. Using Census 2011 (District Census Handbook), NFHS-derived District Nutrition Profile (IFPRI/NITI), NHM facility listings and published studies on migration and tourism in the Kullu valley, we describe demographic composition, migration-related features, health infrastructure, and major health/nutrition burdens. Key findings: Kullu (pop. 437,903 in 2011) remains predominantly rural (~90.6%), with notable seasonal/urban male in-migrant presence in towns (reflected in urban sex ratios and labour patterns); child undernutrition and anemia burdens remain substantial (IFPRI headcount estimates: stunted ~11,855; anemic children ~22,337), while adult women show a double burden of underweight and overweight/obesity. We discuss how limited social integration of migrants (seasonality, language/cultural differences, employment in tourism) may shape access to services and health outcomes, and propose targeted recommendations for inclusive public health action.